2017
DOI: 10.1590/s1678-9946201759051
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent monitoring of Aedes aegypti in a rural area of Rio de Janeiro State, Brazil

Abstract: The aim of this research was to monitor the presence of females of Aedes aegypti (Linnaeus, 1762) on the Seropédica municipality, Rio de Janeiro State, from 2010 to 2013. For this purpose, the Intelligent Dengue Monitoring (IM-Dengue) and Intelligent Virus Monitoring (IM-Virus) developed by Universidade Federal de Minas Gerais (Ecovec – Minas Gerais, Brazil), were used. IM-Dengue is a tool that allows achieving a weekly overview of A. aegypti infestation, while IM-Virus is another tool that allows detecting de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
3
11
0
1
Order By: Relevance
“…Model-based infestation rate estimates were ∼30% higher than those calculated according to ovitrap data [25]. Two studies reported on the meteorological determinants of mosquito presence, and temporal population dynamics [26,27]. Sanavria et al [26] found a strong correlation between temperature and Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-based infestation rate estimates were ∼30% higher than those calculated according to ovitrap data [25]. Two studies reported on the meteorological determinants of mosquito presence, and temporal population dynamics [26,27]. Sanavria et al [26] found a strong correlation between temperature and Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on the meteorological determinants of mosquito presence, and temporal population dynamics [26,27]. Sanavria et al [26] found a strong correlation between temperature and Ae. aegypti presence in autumn (April, May and June) and a moderate correlation during the spring (October, November, December).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, app-technology for the prevention and management of arboviral diseases was less explored. Although there is limited evidence regarding effectiveness, we identified mobile applications which were combined with other approaches such as capacity building, community involvement, traditional vector control methods and others which were effective and feasible as an early warning systems for arboviral disease outbreaks (Sanavria et al, 2017;Palmer et al, 2017) and thus preventing cases (Pepin et al, 2013).…”
Section: Opportunities By Mobile Phone Categoriesmentioning
confidence: 99%
“…have also implemented for tracking and monitoring mosquitoes. For example, a study used mobile phones for submitting ovitrap data to a web database that was able to estimate the index of female Aedes aegypti (Sanavria et al 2017).…”
Section: Outcome Dimensionsmentioning
confidence: 99%